Development of a Tomographic Atmospheric Monitoring System based on Differential Optical Absorption Spectroscopy - Almeida, Rui Filipe Cantarino Valente de (2022)
The aim of this thesis is to describe the design and development of a proof of concept for a commercially viable large area atmospheric analysis tool, for use in trace gas concentration mapping and quanti cation. Atmospheric monitoring is a very well researched eld, with dozens of available analytical systems and subsystems. However, current systems require a very important compromise between spatial and operational complexity. We address this issue asking how we could integrate the Di erential Optical Absorption Spectroscopy (DOAS) atmospheric analysis technique in a Unmanned Aerial Vehicle (UAV) with tomographic capabilities. Using a two-part methodology, I proposed two hypotheses for proving the possibility of a miniaturised tomographic system, both related to how the spectroscopic data is acquired. The rst hypothesis addresses the projection forming aspect of the acquisition, its matrix assembly and the resolution of the consequent equations. This hypothesis was con rmed theoretically by the development of a simulation platform for the reconstruction of a trace gas concentration mapping. The second hypothesis deals with the way in which data is collected in spectroscopic terms. I proposed that with currently available equipment, it should be possible to leverage a consequence of the Beer-Lambert law to produce molecular density elds for trace gases using passiveDOAS. This hypothesiswas partially con rmed, with de nite conclusions being possible only through the use of complex autonomous systems for improved accuracy. This work has been a very important rst step in the establishment of DOAS tomography as a commercially viable solution for atmospheric monitoring, although further studies are required for de nite results. Moreover, this thesis has conducted to the development of a DOAS software library for Python that is currently being used in a production environment. Finally, it is important to mention that two journal articles were published from pursuing this work, both in important journals with Impact Factors over 3.0.